Analysis of Smart Photovolatic Systems - Molnár, Imre; Szodrai, Ferenc (International Journal of Engineering and Management Sciences, 2016)
Nowadays more attention should be paid to the electric power generation wi th renewables. The photovoltaic systems have several benefits. But this systems power output could drastically drop by numerous external phenome. To avoid these, we introduce the so called “TIGO” power opti mizing system features and the monitoring of the deployed system on an existing building. We examine the produced energy for a given time period.